Population structure of the boll weevil in cotton fields and subtropical forests of South America: a bayesian approach - Guzmán, Noelia Verónica (2007)
The main goal of this contribution is to investigate the genetic structure of boll weevil populations from South America (Argentina and Brazil) and to make further comparisons with a putative source population from USA. Samples were collected in a Paranaense forest under reserve protection, cotton fields and non-cultivated areas. Data from anonymous molecular markers were analysed using both traditional methods of population genetics and Bayesian approaches. Results help to support a previous hypothesis on the presence of two lineages of boll weevil populations in South America: one with characteristics of recent invaders and the other with characteristics of ancient populations. The sample from Urugua-i Provincial Park (Misiones, Argentina) shows the highest percentage of polymorphic loci, the highest values of mean heterozigosity, and the largest number of population-specific alleles, all being typical features of ancient populations. Furthermore, the Urugua-i sample shows two gene pools occurring in sympatry, probably as a consequence of a secondary contact. The remaining samples reveal not only lower percentages of polymorphic loci and heterozygosity values, but also an almost negligible presence of specific alleles. Bayesian methods also suggest the occasional migration of some individuals of ancient lineages from their natural habitats in fragments of the Paranaense forest into cotton fields, and vice versa.